2012
DOI: 10.1620/tjem.228.173
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical Features of Two Patients That Progressed from the Early Phase of Chronic Pancreatitis to the Advanced Phase

Abstract: Chronic pancreatitis (CP) has been considered an intractable inflammatory disease that is progressive and irreversible after definite structural changes appear in the pancreas. The Japanese diagnostic criteria for CP were revised in 2009. One of the reasons for this revision was to define a diagnostic criterion for the early phase of CP (early CP) to improve a patient's clinical outcome, because the disease progression might be reversed in this phase by a therapeutic intervention. However, the clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Hirota et al 31 reported distinct clinical features in two patients diagnosed with early chronic pancreatitis, both progressed to definite chronic pancreatitis. Further study is needed to determine whether an instance of early chronic pancreatitis diagnosed using the earlier criteria should be treated as a proven case of chronic pancreatitis, as well as whether abnormal findings can be reversed at this early stage by non-surgical treatments such as abstinence from alcohol, use of oral protease inhibitors, and pancreatic enzyme replacement therapy.…”
Section: Treatment Of Chronic Pancreatitismentioning
confidence: 99%
“…Hirota et al 31 reported distinct clinical features in two patients diagnosed with early chronic pancreatitis, both progressed to definite chronic pancreatitis. Further study is needed to determine whether an instance of early chronic pancreatitis diagnosed using the earlier criteria should be treated as a proven case of chronic pancreatitis, as well as whether abnormal findings can be reversed at this early stage by non-surgical treatments such as abstinence from alcohol, use of oral protease inhibitors, and pancreatic enzyme replacement therapy.…”
Section: Treatment Of Chronic Pancreatitismentioning
confidence: 99%